Silk fibroin scaffolds: A promising candidate for bone regeneration - Wu, Hao; Lin, Kaili; Zhao, Cancan; Wang, Xudong (Frontiers in Bioengineering and Biotechnology, 2022)
It remains a big challenge in clinical practice to repair large-sized bone defects and many factors limit the application of autografts and allografts, making exogenous scaffolds an alternate strategy, among which the silk fibroin (SF) scaffold is a promising candidate. Due to the advantages of excellent biocompatibility, satisfying mechanical property, controllable biodegradability and structural adjustability, SF scaffolds have exhibited great potential in bone regeneration with the help of well-designed structures, bioactive components and functional surface modification. This review will summarize the cell and tissue interaction with SF scaffolds, techniques to fabricate SF scaffolds and modifications of SF scaffolds to enhance osteogenesis, which will provide a deep and comprehensive insight into SF scaffolds and inspire the design and fabrication of novel SF scaffolds for superior osteogenic performance. However, there still needs more comprehensive efforts to promote better clinical translation of SF scaffolds, including deeper understanding of the degradation and clearing mechanisms of different SF scaffolds, further investigation on the degradation products, as well as more experiments in big animal models and clinical researches.